Multi-temporal analysis of land cover changes due to hurricanes Iota and Eta on the islands of San Andres, Providencia and Santa Catalina - Alejandro Álvarez-Echeverry; Luis Jairo Toro-Restrepo; July Andrea Suárez-Gómez; Juan David Osorio-Cano (Dyna)
This study analyzes the how the land cover on the islands of San Andres, Providencia and Santa Catalina, Colombia, was impacted by hurricanes Iota and Eta in 2020. A multitemporal analysis using Sentinel-2 satellite images of the years 2020 and 2021 was conducted to identify changes in land cover and the spectral responses of the NDVI, NDWI, BSI and NBR indices. The results indicate that on Providencia and Santa Catalina the most affected types of land cover were forests, mangroves, secondary vegetation and beaches, particularly in the north and northeast of Providencia and throughout the entire area of Santa Catalina. On San Andres, mangrove forests and grasslands on the eastern and southern coastal edge of the island were the most affected types of cover. This kind of analysis is important to decision makers in coastal land planning because it represents the behavior of land cover in coastal areas in response to disturbances induced by hurricanes, and thus helps us to understand how such extreme natural phenomena influence islands.